MENINGKATKAN KEMAMPUAN PENJUMLAHAN BILANGAN BULAT POSITIF NEGATIF MENGGUNAKAN LIDI BERWARNA PADA SISWA TUNAGRAHITA RINGAN - Yusmaneli - - (Jurnal Penelitian Pendidikan Khusus, 2012)
This Research background overshadow the existence of finding that student of tunagrahita light of class of VII/C SMPLB YPPC Painan amounting to5 people, not yet can do guantifying of positif integer and negative constructively mark with lines number. From is fifth of student exist in class ofVII/c, only one child people capable to sum positive interger and negative by using number line, while is fourth other child not yet can. Intention of thisresearch descriptive about study process and process of make-up of ability of guantifying of positive interger and negative by using chromatic rib media at student of tunagrahita light of class of VII/C in SMPLB YPPC Painan. Method which in using in this research is study of mathematics by using chromatic rib media in the effort improving guantifying of positive integer and negative.